Impact of Digital Navigation on Screening Adherence With the Multi-Target Stool DNA Test - Mallik Greene; Timo Pew; A. Burak Ozbay; John B. Kisiel; A. Mark Fendrick; Paul Limburg (Journal of Health Economics and Outcomes Research, 2025)
# Background Colorectal cancer (CRC) is the fourth most frequently diagnosed cancer and the second leading cause of cancer-related deaths in the United States. Screening can prevent CRC by detecting advanced precancerous lesions. Adherence to screening is crucial in reducing CRC disease burden; however, there is limited research on the impact of digital outreach screening uptake and adherence.